Aortic arch branch-prioritized reconstruction for type A aortic dissection surgery - Gao, Jianfeng; Yan, Jie; Duan, Yanyu; Yu, Junjian; Li, Wentong; Luo, Zhifang; Yu, Wenbo; Xie, Dilin; Liu, Ziyou; Xiong, Jianxian (Frontiers in Cardiovascular Medicine, 2024)
Background: Acute Stanford Type type A Aaortic Dissection dissection (STAAD) is a fatal condition disease that requires requiring urgent surgical intervention. OwingDue to the complexity of the surgical process, various complications, such as neurological disorders, are common. In this study, we prioritized the reconstruction of aortic arch branches during the surgery and investigated the association between the technique of prioritizing the branches and the postoperative outcomes of patients with STAAD.Methods: Ninety-seven97 patients were included in the observational study and underwent total arch replacement and frozen elephant trunk technique betweenfrom January 2018 to and June 2021. Of these, 35 patients underwent the branch branch-priority technique, and 62while 62 patients underwent the classic technique. By analyzing the perioperative outcomes, we compared the differences between the two techniques.The CPB time in the branch priority group had significantly shorter cardiopulmonary bypass (187.4 ± 38.3 vs. 208.5 ± 61.3 min; P < 0.05) was significantly shortened and ventilator times and earlier , postoperative wake-up times (4.1 ± 1.3vs. 6.3 ± 5.6h; P < 0.05) earlier, ventilator time (17.5 ± 8.1 vs. 35.8 ± 13.6 hours; P < 0.05) was lower than that in the classic group. Additionally, the ICU stay time was shorter shorter,(24.3 ± 1.2 vs. 51.1 ± 15.6 hours; P < 0.05), and there was a significant decrease in neurological complications [2 (5.7%) vs. 13 (21.0%); P < 0.05] and 24h drainage (491.5±87.4 vs. 731.5±137.5 ml; P < 0.05). with a significant decrease in neurological complications and 24h drainage in the branch priority group compared to the classic group.